2015
DOI: 10.1080/10942912.2015.1004585
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth Sprouts: A Potential Health Promoting and Nutritive Natural Food

Abstract: Amaranth sprouts are an edible food with good nutritional qualities and potential biological activities of their proteins. The chemical composition, angiotensin converting enzyme inhibitory activity and antioxidant activity of the sprouts were determined. Sprouts showed a protein content similar to the seeds' on a dry basis (16%) and a high fiber content (17%). Amaranth sprout proteins presented a capacity to inhibit angiotensin converting enzyme activity similar to other plant proteins (IC 50 = 0.9 ± 0.6 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
2
19
1
Order By: Relevance
“…It has reported the reducing capability of iron in seeds (55.3 ± 1.6 mg ET/100 g of dry sample) and germinated seeds (122 ± 11.1 mg ET/100 g of dry sample respectively) of Amaranthus caudatus L., without specifying the range; in which differences were observed in the reductive capacity of iron between seeds and germinated seeds, increasing to 2.2 times. 23 In our report, we can see that in general, the germinated increased iron reducing capacity 1.7 times for variety Oscar Blanco and 2.5 times for variety Taray.…”
Section: Discussionsupporting
confidence: 47%
“…It has reported the reducing capability of iron in seeds (55.3 ± 1.6 mg ET/100 g of dry sample) and germinated seeds (122 ± 11.1 mg ET/100 g of dry sample respectively) of Amaranthus caudatus L., without specifying the range; in which differences were observed in the reductive capacity of iron between seeds and germinated seeds, increasing to 2.2 times. 23 In our report, we can see that in general, the germinated increased iron reducing capacity 1.7 times for variety Oscar Blanco and 2.5 times for variety Taray.…”
Section: Discussionsupporting
confidence: 47%
“…Amaranthus caudatus-amaranth 10 PAs, total PC, FC [43] Amaranthus cruentus-amaranth 4, 6, 7 Total PC, AA [44] Amaranthus hypochondriacus-amaranth 2 AA [45] N.S. Carotenoids [46] Chenopodium album-pigweed 48 h AA, total PC [47] 48 h Total PC [48] 48 h Tocopherols [49] Chenopodium quinoa-quinoa Portulaca grandiflora-moss-rose purslane Of course, all of these species, especially the wild ones, will be effectively suitable for sprouting only after solving limitations related to low grain yield and seed dispersal at ripening, and seed dormancy [37].…”
Section: Amaranthaceaementioning
confidence: 99%
“…Only one study has demonstrated the ACE inhibitory capacity of a partially purified 7S-glob subjected to a simulated DGI, with this activity being similar to that of the 11S-glob digests (EC 50 0.17 ± 0.03 mg/ml and 0.17 ± 0.01mg/ml, respectively) (Quiroga et al, 2012). Aphalo et al (2015) reported the ACE inhibitory activity of amaranth sprouts and demonstrated that this activity increases after a simulated DGI (IC 50 0.26 ± 0.07 mg/ml). Vilcacundo et al (2019) have recently subjected a protein concentrate of A. caudatus to a gastrointestinal digestion process using the protocol published by Minekus et al (2014) and analyzed the potential multi-functionality of the released peptides in each digestion stage.…”
Section: In Vitro Assaysmentioning
confidence: 98%
“… Aphalo et al. (2015) reported the ACE inhibitory activity of amaranth sprouts and demonstrated that this activity increases after a simulated DGI (IC 50 0.26 ± 0.07 mg/ml).…”
Section: Bioactive Peptides As Blood Pressure Regulatorsmentioning
confidence: 99%